THE INFLUENCE OF PARENTAL DIVORCE ON THE FORMATION OF PERSONALITY OF TEENAGERS IN ACEH - Keristina Manalu (PT. Lembaga Penerbit Penelitian Nusantara, 2025)
Divorce has been done then this has hurt the gift and also the union that has been given by God and this violates the goal of Christian life which is a mistake and a sin in the eyes of God. The affirmation of the prohibition of divorcing a marriage must always be adhered to and the Lord Jesus said it very clearly